Pengaruh Stres Kerja, Disiplin Kerja dan Promosi Jabatan terhadap Kinerja Karyawan pada PT Capella Multidana Medan - Jurisman Simanjorang; Johan Johan (CERED Indonesia Institute, 2020)
Thus employee performance increase is absolutely necessary as well as the the ability of the organization to control the employee’s stress level,discipline and the promotion of position in the organization as well in order to fulfill the achievement of performance objectives optimally so that the company can survive and win the competition. This research aims to know and analyse the influence of work stress, discipline and job promotion on the performance of employees at Capella Multidana Company Medan. With the Simple Random Sampling technique and using the Slovin formula with 5% percentage of looseness (e), then obtained samples in this study a number of 104 employees who are the status of permanent officers. Data is collected through questionnaire, interviews and documentation studies. The poll is calculated by the measurement unit of Likert scale, and processed using SPSS (statistical product and service solution) program. The results showed that simultaneously, work stress, discipline and job promotion were positively and significantly impacted by the employee performance. Partially, discipline and job promotion were positively and significantly impacted the employee performance but work stress were negatively impacted the employee performance of Capella Multidana Company Medan.